Limits of Reproducing Scientific Traditions in Regional Schools of Thought (On the Material of U.V. Ulyenkova's School of Thought) - Radina N.K (Moscow State University of Psychology and Education, 2018)
The paper presents outcomes of an empirical study aimed at identifying the determinants that influence the preservation of the research agenda in a sci entific school by its followers.The study was carried out on the material of U.V.Ulyenkova's school of thought that has established a unique approach to the diagnostics and treatment of children with delayed mental development.Our hypothesis was that the disciples of this scientific school that carry out their activities within the research agenda and research focus of the school's founder have high levels of research achievements.In the course of the study we identified and followed a network of 42 disciples of Ulyenkova's school of thought and evaluated their research activities, including the indices of their publishing activities in the Russian Science Citation Index.As it was revealed, the preservation of the 'research programme' of the academic supervisor is not common for this network of disciples, and their focus on studying children with delayed mental development is closely connected with citing U.V.Ulyenkova's works and works of other members of the network.We emphasise that the key role is that of the social capital of the postgraduate network: co-authoring, readiness to read and cite works of other followers positively correlates with all the main indices of academic achievements of the explored network.